Determinan Perilaku Merokok Keluarga Penerima Manfaat PKH di Kecamatan Kembangan Jakarta Barat Tahun 2019 - Rini Hariyati; Pujiyanto Pujiyanto; Budi Hidayat (Fakultas Kedokteran Universitas Gadjah Mada, 2021)
Purpose: Program Keluarga Harapan (PKH) is a strategic government program that wants to help the poor meet their health needs. However, there are still PKH beneficiaries who do not understand the health mission of this program. This study intends to explore smoking behavior among PKH families beneficiaries and whether program providers pay attention to promoting healthy living for their beneficiaries. Method: This study uses primary data with cross-sectional design and multiple logistic regression. The number of samples analyzed was 379 households in the Kembangan Region of West Jakarta. Results: Eighty-two percent of PKH recipients were smokers. The four variables related to smoking are low education, low income, smoking psychological dependence, and socially motivated smoking. The psychological and social factors of smoking were among strong predictors and deserve attention in the PKH program. Conclusion: The long-term goal of PKH is to improve the health quality. Smoking reduces the health quality of PKH beneficiaries. The Ministry of Social Affairs needs to coordinate with the Ministry of Health to make this program an entry point for the movement of healthy living in PKH recipient families.